Pathogenicity and antibiotic resistance of Enterococcus faecalis isolated from water used in health-care centers of Ekiti State University and environ - Odeyemi, Adebowale; Omorovie, Paul (International Journal of Biological Research, 2016)
The quality of water samples obtained from the health-care center in the Ekiti State University and three other centers around the campus; Ekiti State University Teaching Hospital (EKSUTH), Iworoko-Ekiti health Centre (IHC) and the State Hospital, Ikole-Ekiti (SHI) were investigated by analyzing the total bacterial count using pour plate method; the incidence and antibiotic resistance of Enterococcus faecalis as water quality indicator was enumerated using selective isolation and disk diffusion method respectively. The mean TBC, TCC and TEC of all the water samples ranged from 9.1 x 102 to 17.4 x 103 CFU/ml, 4.1 x 102 to 5.5 x 103 CFU/ml and 0.4 x 102 to 0.4 x 103 CFU/ml respectively. A total of 70 (32.9%) Enterococcus faecalis were recovered from the water samples from Iworoko HC, which showed highest distribution in bore-hole and well water samples while least frequency of E. faecalis (15.7%) was recovered from EKSU HC. However, no incidence of E. faecalis in table water obtained from all the health-care facilities. Just 35% of 20 selected E. faecalis were caseinase producers while 80% of the isolates were biofilm producers. All the isolates were resistant to cefuroxime, cefixime, augmentin and ceftazidine while only 10% of them were resistant to ofloxacin. 58.6% of the isolates showed MAR to eight (8) antibiotics with three different resistotypes while only 1.4% of them showed MAR to four (4) antibiotics with just one resistotype (CRX-CXM-AUG-CAZ). Only E. faecalis15 among the selected isolates possessed two plasmids with molecular weight of 1.415bp and 13.535bp. However, consumption of contaminated water traceable to faecal sources and plasmid mediated of the causative microbes would be discussed.